Two-factor face authentication: Topographic Independent Component Analysis (TICA) and Multispace Random Projection (MRP) - Lee, Gin Chong; Loo, Chu Kiong; Chockalingam, Letchumanan (IEEE, 2009)
A two-factor face authentication method is presented by using Topographic Independent Component Analysis (TICA) as feature extractor in conjunction with Multispace Random Projection (MRP). Instead of using face alone to access the system, a permissible access requires a pair of genuine face and valid token in authentication mechanism. The formulation is revocable but not reversible and makes replacement effortlessly, hence, offers security reinforcement. Evaluations on TICA as feature extractor before and after MRP have been conducted in the forms of ROC curve, FAR, FRR and scores distribution. The performance of the system has been evaluated under a number of scenarios (normal, stolen token, and stolen face) using Facial Recognition Technology face images.